Status Reinforcement in Emerging Economies: The Psychological Experience of Local Candidates Striving for Global Employment - Al Dabbagh, May; Bowles, Hannah Riley; Thomason, Bobbi (Organization Science, 2016)
In this paper, we explore the psychological experience of university-educated local workers from emerging economies striving to enter the global job market for managerial positions. Building on qualitative data from sub-Saharan Africa and the Arab Gulf, we conducted two experimental studies in the Arab Gulf to test whether local job candidates feel inhibited to self-advocate for higher compensation in global employment contexts and whether they believe that such negotiating behavior is less appropriate in global than in local work contexts. We theorize that shifting from local to global employment contexts, university-educated locals experience a decline in their status as workers because of a perceived lack of fit with the cosmopolitan “ideal worker.” We find that the contrasting global and local labor-market experiences of local job candidates are moderated by gender because local men experience a greater shift in status between local and global employment contexts than do women. This research contributes to the study of status and gender effects on negotiation by illuminating differential constraints of status and gender on negotiating behavior. This research also has important practical implications for the integration and advancement of workers from emerging economies into global institutions and for our broader understanding of how intersecting status-linked social identities influence career negotiations.